Cytological diagnosis of patients with embryonal rhabdomyosarcoma of the cervix: case report and literature review - Xiaoxia Wei; Lei Li (BMC, 2024)
Abstract Cervical embryonal rhabdomyosarcoma(ERMS) is a rare malignancy. To date, no cases of ERMS diagnosed by cervical cytology have been reported. In this study, we report a case of cervical ERMS identified by a liquid-based cytology test and cell blocks in a 46-year-old postmenopausal woman. We describe the cytological features of ERMS, with the aim of helping cytopathologists recognize this rare cervical tumor.